Genetic variability in and effects of N-Fertilizer on seed protein content of long bean - Mak, C.; Yap, T. C. (Malaysian Society of Applied Biology, 1977)
Considerable genetic variability existed in percent seed protein, pod yield, yield components and some vegetative characters among 8 local and 14 foreign cultivars of long bean evaluated. An increase of 400 kg/ha. N-fertilizer caused a mean rise of about 3% in seed protein content. However, the ranking of high and low protein varieties was similar for the different levels of N-fertilizer. No correlation was found between seed protein content and yield. Pod yield was highly associated with yield components. Breeding for simultaneous improvement of pod yield and seed protein is discussed.